Antioxidant Activity of Ethanol Extract of Kepok Banana Peel (Musa paradisiaca L.) by Ferric Reducing Antioxidant Power Method - Damang, Irda Binti; Suhaenah, Asriani; Razak, Rais (Pharmaceutical Reports, 2025)
Antioxidants are compounds capable of neutralizing the harmful effects of oxidants by donating electrons to unstable molecules, thereby preventing oxidative damage. These compounds play a vital role in protecting biological systems from oxidative stress, which is associated with aging and various chronic diseases. Kepok banana (Musa paradisiaca Linn.) peel is an underutilized natural resource rich in secondary metabolites such as saponins, flavonoids, alkaloids, tannins, and quinones, many of which are known for their strong antioxidant potential. The present study aimed to evaluate the antioxidant activity of the ethanol extract of kepok banana peel using the Ferric Reducing Antioxidant Power (FRAP) method. Extraction was performed by maceration with 96% ethanol as the solvent to obtain a concentrated extract. The FRAP assay was carried out by reacting the extract with FRAP reagents and measuring the absorbance using a UV–Vis spectrophotometer at a maximum wavelength of 710 nm. Quercetin was used as a standard antioxidant reference, producing a calibration curve with a linear regression equation of y = 0.0203x + 0.0301 and a correlation coefficient (r) of 0.9965, indicating excellent linearity. The results revealed that the ethanol extract of kepok banana peel exhibited high antioxidant capacity, with a value of 81.6939 mgQE/g extract. These findings suggest that kepok banana peel is a promising natural source of antioxidants and could potentially be developed into functional ingredients for pharmaceutical and nutraceutical applications.